2020
DOI: 10.1101/2020.09.23.310839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SpRY greatly expands the genome editing scope in rice with highly flexible PAM recognition

Abstract: Plant genome engineering mediated by various CRISPR-based tools requires specific protospacer adjacent motifs (PAMs), such as the well-performed NGG, NG, NNG, etc., to initiate the target recognition, which notably restricts the editable range of the plant genome. In this study, we thoroughly investigated the nuclease activity and the PAM preference of two structurally-engineered SpCas9 variants (SpG and SpRY) in transgenic rice. Our study shows that SpG nuclease favors NGD PAMs, albeit less efficiently than t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(61 reference statements)
0
4
0
Order By: Relevance
“… 31 In the future, it will be worthwhile to attempt this experiment again with base editors, such as evoAPOBEC1-BE4max and BE4-SsAPOBEC3B models, which have been designed with these new enzymes (allowing high and precise deamination and reducing off targets), or NG-Cas9, SpG, and SpRY (having a non-specific PAM). 22 , 33 , 34 , 35 These enzymes have also been designed to have a narrower conversion window, which could be used to favor C2 editing. We hope that the recent development of the Prime editing technology might allow us to modify only the C2 nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“… 31 In the future, it will be worthwhile to attempt this experiment again with base editors, such as evoAPOBEC1-BE4max and BE4-SsAPOBEC3B models, which have been designed with these new enzymes (allowing high and precise deamination and reducing off targets), or NG-Cas9, SpG, and SpRY (having a non-specific PAM). 22 , 33 , 34 , 35 These enzymes have also been designed to have a narrower conversion window, which could be used to favor C2 editing. We hope that the recent development of the Prime editing technology might allow us to modify only the C2 nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cas9-NG, ScCas9 and iSpyMacCas9 were applied to plants, using NG, NAG, and NAAR PAMs, respectively (Hua et al 2019;Sretenovic et al 2020;Wang et al 2020c). Also, the development of SpRY with very low PAM restriction was applicable for BEs in plants (Ren et al 2021;Walton et al 2020;Xu et al 2021). BE by Cas12a or its PAM altered variants has been successfully performed in human cells (Kleinstiver et al 2019;Li et al 2018a), but has not been reported in plants to date.…”
Section: Advances Of the Base Editing Techniquementioning
confidence: 99%
“…The researchers further optimized SpG to develop SpRY that has the potential of targeting almost all PAM. Xu et al (2020a) have researched the effectiveness of both SpG and SpRY nucleases against separate PAMs and their use in both cytosine and adenine base editing using transgenic rice callus. They reported that even though SpG recognizes NG PAM sequences, its performance is less when compared to SpCas9-NG in rice.…”
Section: Pamless Base Editorsmentioning
confidence: 99%